Monitoring endophyte populations in pine plantations and native oak forests in Northern Spain - Martínez-Álvarez, P.; Rodríguez-Ceinós, S.; Martín-García, J.; Diez, J. J. (Forest Systems, 2012)
Replacement of native forest with plantations of other species can have important consequences over the ecosystem. Some of these changes have been widely studied, but very little information is available about what happen with fungal communities and specifically with endophyte species living there. In this work endophyte assemblages of pine plantations (Pinus sylvestris, P. nigra and P. pinaster) are compared with those found in the original oak forest (Quercus pyrenaica) of the study area (north of Palencia province, Spain). For this purpose, samples of needles/leaves and twigs from three trees in each one of the three plots sampled per host species, were first collected and later processed in the lab to detect all endophyte species living there. Besides an intensive data compilation was realized in the twelve sites studied to analyze the environmental, crown condition, dendrometric and soil variables involved in the distribution of the fungi. Endophyte assemblages of P. nigra and P. sylvestris resulted to be closer, and at the same time separated from the ones of P. pinaster and Q. pyrenaica. In addition, some variables were found to be related to the endophyte communities’ distribution. Finally, a change in the endophyte communities was detected due to the deterioration and replacement of native oak forests with pine plantations.